2021
DOI: 10.1098/rspb.2020.2504
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced problem-solving ability as an adaptation to urban environments in house mice

Abstract: Humans have a large impact on the distribution and abundance of animal species worldwide. The ecological effects of human-altered environments are being increasingly recognized and understood, but their effects on evolution are largely unknown. Enhanced cognitive abilities and the ability to innovate have been suggested as crucial traits for thriving in human-altered habitats. We tested if house mice ( Mus musculus ) subspecies have evolved enhanced innovative problem-solving abilities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 43 publications
0
11
1
Order By: Relevance
“…However, we included one test where the birds had to remove an obstacle to enter their nest instead of accessing food, because it still required the bird to manipulate an obstacle to access a reward, thus presumably required similar cognitive and motoric skills to the food access tests (Preiszner et al, 2017). We also decided to exclude papers that, rather than comparing urban and non-urban populations of the same species, defined "urbanization" as the distance from the edge of a residential area (Grunst et al, 2020) or compared subspecies with different history in urban habitats (Vrbanec et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, we included one test where the birds had to remove an obstacle to enter their nest instead of accessing food, because it still required the bird to manipulate an obstacle to access a reward, thus presumably required similar cognitive and motoric skills to the food access tests (Preiszner et al, 2017). We also decided to exclude papers that, rather than comparing urban and non-urban populations of the same species, defined "urbanization" as the distance from the edge of a residential area (Grunst et al, 2020) or compared subspecies with different history in urban habitats (Vrbanec et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Morphological adaptations such as longer tails as well as changes in behavior and life history have been described previously (Berry, 1981;Pockock et al, 2005). Behaviors associated with flexibility (i.e., innovation propensity and inhibitory control) are heightened in house mouse subspecies that have lived together with humans for longer (Vrbanec et al, 2021). In addition, Frynta et al (2018) found commensal populations to show increased exploration behavior of elevated places over non-commensal house mouse populations.…”
Section: Introductionmentioning
confidence: 58%
“…While all M. musculus were caught in or close to human buildings, M. spicilegus and A. uralensis were never caught in human buildings but on agricultural fields. Detailed information including GPS locations of trapping sites can be found in Harr et al (2016) and Vrbanec et al (2021).…”
Section: Animals and Housing Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, bird species that show a greater propensity for innovation are more likely to become established invaders worldwide ; see also Roudez et al 2008;Damas-Moreira et al 2019;Ortiz-Alvarado and Rivera-Marchand 2020). Similar mechanisms have also been connected to successful invasion of urban areas (Audet et al 2015;Cook et al 2017;Kozlovsky et al 2017;Lee and Thornton 2021;Vrbanec et al 2021). On a larger evolutionary timescale, behavioral flexibility has been suggested to facilitate adaptive radiation on islands by enabling species to persist in new niches that are eventually entrenched via selection .…”
Section: Introductionmentioning
confidence: 93%